Apelin receptor inhibition in ischemia-reperfused mouse hearts protected by endogenous n-3 polyunsaturated fatty acids - Shuang Zheng; Weijiang Tan; Weijiang Tan; Xiang Li; Xiang Li; Lijing Wang; Caiyi Zhu; W. Glen Pyle; W. Glen Pyle; Jianxin Chen; Jian Wu; Xuecong Ren; et al. (Frontiers Media S.A., 2023)
Background: While the protective effects of n-3 polyunsaturated fatty acids (PUFAs) on cardiac ischemia-reperfusion (IR) injury have been previously reported, limited data are available regarding how these fatty acids affect membrane receptors and their downstream signaling following IR injury. We aimed to identify potential receptors activated by n-3 PUFAs in IR hearts to understand the regulatory mechanisms of these receptors.Methods: We used fat-1 mice, which naturally have elevated levels of n-3 PUFAs, and C57BL/6J mice as a control group to create a myocardial IR injury model through Langendorff perfusion. We assessed the impact of endogenous n-3 PUFAs on left ventricular function, myocardial infarct size, myocardial apoptosis, and ATP production. RNA sequencing (RNA-seq) and bioinformatics analysis were conducted to identify molecular targets affected by n-3 PUFAs. Based on these analyses we then treated IR hearts of WT and fat-1 mice with an antagonist (ML221) or an agonist (apelin-13) for the predicted receptor to assess cardiac contractile function and intracellular signaling pathways. An in vitro hypoxia-reoxygenation (HR) model was also used to confirm the effects of n-3 PUFAs on the examined intracellular signaling pathways.Results: Endogenous n-3 PUFAs protected cardiac structure and function in post-IR hearts, and modulated phosphorylation patterns in the PI3K-AKT-mTOR signaling pathways. RNA-seq analysis revealed that n-3 PUFAs affected multiple biological processes as well as levels of the apelin receptor (APLNR). Consistent with a role for the PLNNR, ML221 synchronized the activation of the PI3K-AKT-mTOR signaling axis, suppressed the expression of PKCδ and phosphorylated p38α, upregulated PKCε expression, upregulated or restored the phosphorylation of myofilaments, and prevented myocardial injury and contractile dysfunction in WT IR hearts. By contrast, apelin-13 disrupted the PI3K-AKT-mTOR signaling axis in post-IR fat-1 hearts. The phosphorylation signaling targeted by APLNR inhibition in post-IR fat-1 hearts was also observed after treating HR cells with eicosatetraenoic acid (EPA).Conclusion: Endogenous n-3 PUFAs protect against post-IR injury and preserve cardiac contractile function possibly through APLNR inhibition. This inhibition synchronizes the PI3K-AKT-mTOR axis, suppresses detrimental phosphorylation signaling, and restores or increases myofilament phosphorylation in post-IR hearts. The beneficial effects observed in fat-1 transgenic mouse hearts can be attributed, at least in part, to elevated EPA levels. This study is the first to demonstrate that n-3 PUFAs protect hearts against IR injury through APLNR inhibition.